2015
DOI: 10.1002/2015jd023871
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of aerosol particles and light extinction apportionment before and during the heating season in Beijing, China

Abstract: Despite extensive efforts into characterization of the sources and formation mechanisms of severe haze pollution in the megacity of Beijing, the response of aerosol composition and optical properties to coal combustion emissions in the heating season remain poorly understood. Here we conducted a 3 month real‐time measurement of submicron aerosol (PM1) composition by an Aerosol Chemical Speciation Monitor and particle light extinction by a Cavity Attenuated Phase Shift extinction monitor in Beijing, China, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 75 publications
9
53
3
Order By: Relevance
“…S6c). This is similar to the composition reported in Wang et al 29 who showed that coal combustion emissions had a dominant impact on these species. In fact, the difference in OA composition was dominated by CCOA, accounting for 45% and 53% during D3 and D4, respectively (Fig.…”
supporting
confidence: 91%
“…S6c). This is similar to the composition reported in Wang et al 29 who showed that coal combustion emissions had a dominant impact on these species. In fact, the difference in OA composition was dominated by CCOA, accounting for 45% and 53% during D3 and D4, respectively (Fig.…”
supporting
confidence: 91%
“…The meteorological parameters, temperature (T) and relative humidity (RH) at ground site, and wind direction (WD) and wind speed (WS) at 240 m were obtained from the measurements on the Beijing 325 m meteorological tower. More detailed descriptions of the sampling site, the operations of the ACSM, and the collocated 5 measurements are given elsewhere Ge et al, 2013;Wang et al, 2015).…”
Section: Samplingmentioning
confidence: 99%
“…A recent study showed the comparable contributions between SOA and SIA in severe haze pollution in China, highlighting the importance of SOA in haze formation (Huang et al, 2014). However, previous studies also found that POA was more important than SOA in heating season due to enhanced coal combustion emissions Wang et al, 2015). However, most of these measurements were conducted at ground sites, which are subject to the influences of local source emissions.…”
Section: Introductionmentioning
confidence: 99%